(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
Ermanno Sangiorgi, head of the Palermo police (Questore) since 1898, described in his police reports (a thick archival file of about 500 handwritten pages) a detailed portrait of the network of mafia groups emerging in the Seventies of the XIX century in the rich area around Palermo. In spite of the rich and solid information, his enquiries have been neglected until the late XX century and its judicial outcomes that developed in the same years of the Notarbartolo case, considered unimportant. The recent book by Umberto Santino (La mafia dimenticata. La criminalità in Sicilia dall’Unità d’Italia ai primi del Novecento. Le inchieste, i processi. Un documento storico. Melampo, Milano, 2017, pp. 643), publishes the source in the framework of the public debate about mafia in Liberal Italy, aiming at revaluating the contribution that he gave to the knowledge about the emerging mafia phenomenon. The article discusses issues concerning the police source, its production and judicial outcomes, and its relationship with the public and scientific debates about mafia. Keywords: Mafia; history of police in Liberal Italy; Rapporto Sangiorgi